qanda-logo
search-icon
Símbolos
Problema
solution-image
$2$ Utiliza los polinomios anteriores para efectuar RESTAS: a) $\right)$ $\left(x^{3}-3x^{2}+4x-1\right)-\left(5x^{3}+x^{2}-x+6\right)=$ b) $\left(x^{4}+2x^{2}+4\right)-\left(2x^{3}-2x^{2}-5x+1\right)=$ $c\right)\left(x^{3}-4x^{2}-3x+5\right)-\left(2x^{3}+4x^{2}-x+2\right)=$ $d\right)$ $\left(3/4x^{5-1/2x^{4-3x^{2}}}\right)-\left(2x^{4-5x+1}\right)+\left(5x3-2/5x6\right)=$ $e\right)$ $\left(2x\right)-\left(3x^{2}\right)=$
Bachillerato
Aritmética y álgebra
Búsquedas: 148
Solución
answer-user-profile-image
Profesor de Qanda - Luis
answer-reply-image